Budaya Berbusana Batik pada Generasi Muda - Sanjaya, Fony; Yuwanto, Listyo (Universitas Brawijaya, 2019)
Batik is the world's cultural heritage that is recognized as originating from Indonesia. Nowadays batik becomes a lifestyle for the young generation. Batik lifestyle behavior can be explained through the theory of planned behavior. The aim of this study was to investigate the intentions of using batik among members of the younger generation based on their attitudes towards batik, subjective norms about batik, and control of batik lifestyle behavior. The study was conducted by giving an opened questionnaire to 30 respondents consisting of 7 men and 23 women in the East Java area. This step is accompanied by a semi-structured interview that was conducted with two respondents. The results of the questionnaire show that there are several factors that encourage the younger generation to dress in batik, including aesthetics, prestige, fashionable, national identity, and flexibility. The aesthetic value of batik is the main intention to dress batik among members of the younger generation, which is driven by their attitudes towards batik and control of batik lifestyle behavior. The current research also shows that family is the driving factor (subjective norm) for the young generation to dress in batikBatik merupakan warisan budaya dunia yang diakui berasal dari bangsa Indonesia. Dewasa ini batik menjadi gaya hidup berbusana generasi muda. Perilaku berbusana batik dapat dijelaskan melalui theory of planned behavior (teori perilaku terencana). Penelitian ini bertujuan untuk mengetahui intensi berbusana batik pada generasi muda yang didasari oleh sikap terhadap batik, norma subyektif tentang batik, dan kontrol terhadap perilaku berbusana batik. Penelitian dilakukan dengan memberikan angket terbuka kepada 30 orang responden yang terdiri dari 7 orang laki-laki dan 23 orang perempuan di area Jawa Timur. Setelah itu dilakukan wawancara semi terstruktur kepada 2 orang dari responden tersebut. Hasil angket menunjukkan faktor-faktor yang mendorong generasi muda berbusana batik yaitu nilai estetika, prestise, fashionable, identitas bangsa, dan fleksibilitas. Nilai estetika pada batik merupakan intensi utama menggunakan pakaian batik pada generasi muda yang diprediksi oleh sikap terhadap batik dan kontrol terhadap perilaku berbusana batik. Penelitian ini juga menemukan bahwa keluarga adalah faktor pendorong (norma subyektif) generasi muda menggunakan batik